Co-existence of peripheral fatigue of the knee extensors and jump potentiation after an incremental running test to exhaustion in endurance trained male runners - Gonzalo Márquez; Jorge González-Hernandez; Pedro Jiménez-Reyes; David Colomer-Poveda; Daniel Boullosa (Frontiers Media S.A., 2023)
The aim of the present study was to investigate the effect of an incremental running exercise until exhaustion on twitch responses and jump capacity in endurance trained runners. For this purpose, 8 experienced endurance male runners were required to perform neuromuscular function tests before and after a submaximal running bout (control condition -CTR-) or an incremental running test to volitional exhaustion (experimental conditions -EXP-). The twitch interpolation technique was used to assess voluntary activation and muscle contractile properties before and after each condition (CTR and EXP). Countermovement jump was also used to assess the stretch-shortening cycle function before and after both conditions. In addition, rating of perceived exertion, heart rate, blood lactate and skin temperature were also recorded. Only EXP improved jump performance, however, it was also accompanied by a reduction in maximal voluntary contraction and the peak twitch force of the knee extensors evoked by electrical stimulation at 10 Hz (Db10). It is likely that reductions in maximal voluntary contraction may be related to an excitation-contraction coupling failure (i.e. low-frequency fatigue) as suggest the reduction in the Db10. The current results confirm that acute changes in jump performance may not be appropriate to evaluate acute fatigue in endurance trained runners.